Do foreign experts increase the productivity of domestic firms? - Nikolaj Malchow-Møller; Jakob R. Munch; Jan Rose Skaksen (Institute for the Study of Labor (IZA), 2011)
While most countries welcome (and some even subsidise) high-skilled immigrants, there is very limited evidence of their importance for domestic firms. To guide our empirical analysis, we first set up a simple theoretical model to show how foreign experts may impact on the productivity and wages of domestic firms. Using matched worker-firm data from Denmark and a difference-indifferences matching approach, we then find that firms that hire foreign experts - defined as employees eligible for reduced taxation under the Danish Tax scheme for foreign researchers and key employees - both become more productive (pay higher wages) and increase their exports of goods and services.
urn:nbn:de:101:1-201110263393
Keywords: F22; J24; J31; J61; L2; 330; foreign experts; export; immigrants; productivity; difference-in-differences matching; Hochqualifizierte Arbeitskräfte; Sachverständige; Ausländische Arbeitskräfte; Einwanderung; Unternehmensentwicklung; Produktivität; Dänemark